THE EFFECT OF PICTURE SERIES ON STUDENTS’ ACHIEVEMENT IN WRITING RECOUNT - Lubis, Hindun; Sihite, Meida Rabia; Zulkarnain, Iskandar (Jurnal Warta Dharmawangsa, 2023)
The objective of this research is to find out The Effect of Picture Series on Students’ Achievement in Writing Recount. The design applied in this research was experimental research design.  This research was conducted in X grade at MAS Alwashliyah 12 Perbaungan Academic Year 2022-2023 . There were two classes of X grade. Each class consisted of 32 students. So, the total number of population were 64 students. Cluster-sampling technique was employed in taking the sample. X -2 was selected as experimental group and X  -1 was selected as control group. There are 64 students were chosen as the sample. The instrument used to collect the data was writing test. The data were analyzed by using t-test. After the data had been analyzed, it was obtained tobserved value  was higher than that of ttable (1.57 > 1.671) with the degree of freedom df = 58 at the level of significance α = 5. It meant that Ha was accepted and Ho was rejected. In conclusion, Picture Series significantly affected on students’ achievement in writing recount. Keywords: Picture Series, Writing, Recount .